Employers’ behavioural responses to the introduction of an apprenticeship levy in England: an ex ante assessment - Gambin, Lynn [Verfasser]; Hogarth, Terence [Verfasser] (My University, 2021)
"An apprenticeship levy was introduced in England in 2017 to help the government meet its target of 3 million apprenticeships between 2015 and 2020. Training levies have been, until recently, something of an anathema in public policy circles in England with most having been abolished by the mid-1980s as the government moved towards creating a flexible, de-regulated labour market. So why would an apprenticeship levy now produce better results? In this paper, we analyse in-depth employer interviews carried out in 2016 to identify possible impacts of the levy on businesses’ approaches to apprenticeships. We consider whether, ex ante, the levy was expected to result in: more apprentices being trained; reconfiguration of existing training structures into apprenticeships; employers ‘gaming’ the system, with levy funds being used but not producing real gains in training; or, employers writing off the levy. These findings are presented alongside data on apprenticeship starts since the levy’s introduction. We discuss the dramatic fall in apprenticeship starts relative to pre-levy numbers. Given the latest figures and our ex ante study of employers, it appears as though even such wide-sweeping change to the programme may do little to overcome longstanding, low levels of employer demand for apprenticeships." (Author's abstract ; BIBB-Doku)
Keywords: S 4.1.4 Fonds- und Umlagefinanzierung; G 1.3.1.1 Ausbildungsstellenmarkt; S 3.2 Unternehmen und Behörden; I 2.2.1 Westeuropa; 370; Berufsbildung; Ausbildungsplatzabgabe; Ausbildungsstellenmarkt; Ausbildungsbetrieb; Berufsbildungsstatistik; Großbritannien